Coherent parametric X-radiation by the train of charged particles bunches: Conditions of observation; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Babaev A. A. Anton Anatoljevich (2017, 2017)
Title screen